Getting the Correct Answer - Gladys Sterenberg (University of Windsor, 2006)
This paper investigates the question: What does it mean to experience correctness in school mathematics? Drawing on interviews and observations of classroom interaction, the author describes possible experiences of students when they get an answer, when they cannot get the correct answer, and when they get the right answer but do not understand how they got it. Questions surrounding student perseverance in getting the correct answer and the relationship between power and the possession of a correct answer are considered. Emerging issues of schools as correctional institutions, teachers and textbooks as sole authorities, and mathematical truth and rightness as absolutes are discussed. Through a phenomenological consideration of the embodied experiences of students, the author challenges the prevalent preoccupation with correctness and offers an alternative pedagogy that is informed by a sense of ethics rather than correctness. As students begin to view correctness as embedded in incorrectness, maybe their experiences of ambiguity and uncertainty can be welcomed. Perhaps school mathematics can embrace human experiences.